The Republic of Congo's Infrastructure : A Continental Perspective - Pushak, Nataliya (World Bank, Washington, DC, 2017)
Upgrading infrastructure plays a critical role in the Republic of Congo's quest to diversify its economy and reduce poverty. It is also an important source of growth on its own. A cross-country statistical analysis conducted for this report shows that infrastructure contributed one-half of one percentage point to the Republic of Congo's per capita gross domestic product (GDP) growth annually from 2001 to 2006. However, if the country's infrastructure could be improved to the level seen in Mauritius, the leading country in Sub-Saharan Africa, it could contribute more than 3 percentage points to annual per capita growth. The Republic of Congo's power infrastructure is inadequate and inefficiently operated. The country lags well behind peer countries in generation capacity and electrification. The parts of the population not served by the grid face exorbitant costs. The government has responded to these issues with an ambitious investment plan. However, if new assets are to operate effectively, major inefficiencies in the power utility will also need to be addressed. The utility's transmission and distribution losses are 47 percent, more than double best-practice benchmarks, while the cost of overstaffing is 30 percent of utility revenue. Tariffs recover barely half the cost of service provision, even though full cost recovery will be affordable to the population. In the information and communication technology (ICT) sector, the Republic of Congo has made good progress in developing its mobile telephony market in recent years, with high levels of signal coverage. The cost of international connectivity is currently high, but it should fall once the country connects to the international submarine cable and completes its domestic fiber optic network. On the other hand, the physically dilapidated and financially depleted condition of the fixed-line telephone operator is becoming a constraint to raising Internet penetration. The Republic of Congo performs relatively well on service coverage in the water and sanitation sector. The country's access statistics are substantially ahead of those in its peer group, particularly with regard to piped water, stand-posts, and improved latrines. However, access to services is much greater in urban areas than in rural areas. Furthermore, under-pricing of water has hurt the financial soundness of the water utility, even though analysis suggests that cost recovery tariffs would be affordable to consumers.